HAMKA SEBAGAI KETUA UMUM MUI (MAJELIS ULAMA INDONESIA) DALAM MENGHADAPI MASALAH SOSIAL POLITIK PADA MASA ORDE BARU 1975-1981 - Wildan Insan Fauzi (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
Feeling the need for an alternative channel of communication with the Muslim community, in 1975 the government established a national Council of Ulama, the ‘Majelis Ulama Indonesia’ (MUI). MUI was establish to some purpose like mobilising Muslim support for the government’s development policies, although officially meant to facilitate two-way communication, in practice the council’s function is, as aptly formulated by the present Minister of Religion, “to translate government policy into a language that the ummah understands, Its functions are reminiscent of the traditional office of the shaykh al-islam, issuing fatwa to legitimise government policies; its ability to modify these policies is only very marginal.